Statutory regulation of small and medium-scale entrepreneurship in Kazakhstan - Khamzin, Y.; Moldabayev, R. (World Applied Sciences Journal 25 (5), 827-831, 2013)
In this article, the issues of statutory regulation of small- and medium-scale entrepreneurship in Kazakhstan were analyzed. The problems of a business in its function as an object of right and a subject of entrepreneurial activity were considered. The circumstances of the development of small- and medium-scale entrepreneurship in Kazakhstan were analyzed. This article also deals with the issues of participation of selfemployed entrepreneurs in the sphere of small- and medium-scale entrepreneurship. Statistic data of the Agency for Statistics of the Republic of Kazakhstan are provided with respect to the growth of the share of small- and medium-scale entrepreneurship in the GDP.
Keywords: Entrepreneurial activity; Entrepreneurship in the Republic of Kazakhstan; Legislation of the Republic of Kazakhstan; Self-employed entrepreneur